PENERAPAN PERMAINAN TRADISIONAL TEROMPAH PANJANG UNTUK MENINGKATKAN KELINCAHAN DAN SPORTIVITAS SISWA PADA MATERI AKTIVITAS KEBUGARAN - Aldora Pratama; Riko Amrullah; Rahmat Syawallul Fikri; Ashabul Kahfi; Rezy Risky Pratama (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This article describes the implementation of the traditional game terompah panjang in physical education learning on fitness activity material at SD Negeri 158 Palembang. The study was written from the experience of School Field Introduction Program students from the Faculty of Teacher Training and Education, Universitas PGRI Palembang. A descriptive qualitative approach was used because the focus of the article was to present the learning process naturally, not to measure student achievement with numerical data. Data were collected through direct observation, photo documentation, and field notes during the learning activity. The results showed that terompah panjang provided a meaningful movement experience for students. During the game, students were encouraged to move actively, maintain balance, adjust their steps, and coordinate their body movements with the rhythm of their group. The activity also created opportunities for students to practice cooperation, communication, discipline, and sportsmanship. Based on observation, students began to show more directed movements when they followed group instructions and maintained a shared rhythm. Their sportsmanship appeared through obeying rules, waiting for turns, encouraging friends, and accepting the game results. Therefore, terompah panjang can be used as an alternative learning medium that combines physical activity, local culture, and character education in physical education.